PENGEMBANGAN ECOLITERACY MELALUI PROGRAM BANK SAMPAH: SEBAGAI UPAYA MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) - Anggraeni, Ira; Yanti, Irma (Jurnal Anak Bangsa, 2024)
This study aims to develop ecoliteracy in early childhood students through the implementation of the Waste Bank Program at PAUD Kober Al-'Urwatul Wutsqa, which consists of 45 students. This program introduces the concept of waste sorting, recycling, and waste management as part of environmental-based learning. The method used is qualitative descriptive research with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that the Waste Bank Program has succeeded in improving students' understanding and behavior towards the environment, where they are starting to be able to sort waste and understand the importance of maintaining cleanliness and reducing waste. In addition, this program also supports the achievement of several Sustainable Development Goals (SDGs), such as quality education (Goal 4), responsible consumption and production (Goal 12), and action on climate change (Goal 13). Thus, this program has proven effective in instilling sustainability values ​​in students from an early age and can be a model for implementation for other schools